Assessment of speaking interaction: Rater perception and testing criteria in Japanese elementary English education - Otsuki, Yuki (Neofilolog, 2025)
This study aimed to explore assessment criteria for speaking interactions in performance tests conducted under the curriculum of formal elementary school English education in Japan, that are intended to foster students’ communicative competence in an authentic language use environment. Building on the framework of Sato and McNamara (2018), a qualitative analysis of rater perceptions of communicative elements of young learner oral interaction was conducted. The current study examined the perception of nine raters. The material for analysis consisted of transcripts from video recordings of the elementary school students’ role-play test. The findings indicated that the flow of interaction had a particularly strong impact on raters, along with five other factors. Perceptions of the use of L1 and nonverbal behaviors were nuanced, and only sometimes viewed favorably. Furthermore, in interaction involving limited vocabulary and use of formulaic expressions, speed was not always perceived positively and was occasionally seen as rote memorization. These insights could be applied in the holistic assessment of speaking tests in young beginner learners.